0424 The Injury Prevention Effects of Regulatory Workplace Safety Inspections in British Columbia, Canada from 2001 to 2011. (23rd June 2014) - McLeod, Kim; McLeod, Chris; Koehoorn, Mieke; Davies, Hugh; Amick, Benjamin
Abstract : Objectives: To determine if inspections by the workplace safety regulator (WorkSafeBC) in the Canadian Province of British Columbia are associated with a reduction in firm injury rates. Method: Injury, inspection, and claims data collected by WorkSafeBC were analysed to determine the lost-time rates for all single-location firms that had been in operation in British Columbia for at least four years between the years of 2001 and 2011. Log-linear generalised estimating equations analyses were conducted to examine the effect of a workplace inspection on the change in injury rates between the year of inspection and the following year. Models were adjusted for time and sector. Results: 74 510 firms met the eligibility criteria, with about 3% of firms per year experiencing an inspection, over the time period of 2001 to 2008. The ratio of firms inspected varied by sector, for example, about 8% of primary resources firms were inspected per year during this same period. Inspected firms had a higher injury rate (10 SLF claims per 100 FTE annually) compared to non-inspected firms (4 claims per 100 FTE). Through GEE analyses, it was found that an inspection reduced injuries (beta coeff= -0.0048 (-0.0067, -0.0029)) in the year following an inspection. The effect was greater for larger (>=10FTE) (beta coeff=-0.015 (-0.021, -0.009)) versus smaller firms (<10FTE) (beta coeff= -0.0067 (-0.0094, -0.0040)). Conclusions: These results suggest that inspections do have injury prevention effects, and the differing effects by firm characteristics may indicate the opportunity to target firms according to the most appropriate intervention.